The relationship between urban residents’ physical exercise attitudes and sports consumption demands: the mediating role of physical activity level - Chen, WeiSong; Zhou, Bowei; Peng, Bo; Li, Lin (Frontiers in Psychology, 2024)
Object This study examines the differences and relationships among urban residents’ physical exercise attitudes, physical activity levels, and sports consumption demands, focusing on how physical activity mediates the relationship between exercise attitudes and consumption behaviors. Method A survey was conducted among residents in Chengdu using validated questionnaires to measure physical exercise attitudes, physical activity levels, and sports consumption demands. Data analysis included independent samples t-tests and one-way ANOVA to assess differences across demographic variables, as well as correlation analysis and structural equation modeling to examine the path relationships among key variables. Results Independent samples t-tests and ANOVA showed significant differences in sports consumption demands across age, education, and income groups (p < 0.05). Correlation analysis revealed significant positive relationships among physical exercise attitudes, physical activity levels, and sports consumption demands (p < 0.01). Structural equation modeling confirmed that physical activity levels partially mediated the relationship, with a direct effect size of 0.295 (p < 0.001) and an indirect effect size of 0.117 (p < 0.001), accounting for 28.4% of the total effect. Conclusion The study highlights that positive exercise attitudes significantly impact sports consumption demands directly and through the mediating role of physical activity levels. Enhancing physical activity can amplify the effects of exercise attitudes on consumption, providing insights for promoting sports participation and consumption in urban settings.